IMF Survey : Volume 28, Issue 06. (IMF Survey; IMF Survey ;, 1999)
In a statement issued on March 8, IMF Managing Director Michel Camdessus announced his intention to recommend to the IMF Executive Board that it approve the revised economic program for 1999-2001 proposed by the Brazilian government. The text of News Brief 99/10 follows.